Biomediated recycling of aerated concrete waste into thermally-insulating living building materials - Hamdy A. Abdel-Gawwad; Alaa A. Saleh; Hamada Shoukry; Ahmed A. Radwan; Mohammed Abd Elrahman; Ahmed E. Zoheir (Chemical Engineering Journal, 2025)

Efficient adsorption of hexavalent chromium ions onto novel ferrochrome slag/polyaniline nanocomposite: ANN modeling, isotherms, kinetics, and thermodynamic studies - Mohammed Ilyas Khan; Mohammed Khaloufa Almesfer; Abubakr Mustafa Elkhaleefa; Abdelfattah Aamary; Ismat Hassan Ali; Mohammed Zubair Shamim; Hamada Shoukry; Mohmmad Rehan (Environmental Science and Pollution Research, 2022)

Reuse of lead glass sludge in the fabrication of thermally insulating foamed glass with outstanding properties and high Pb-stabilization - Hamdy A. Abdel-Gawwad; Mona S. Mohammed; Mohammed A. Arif; Hamada Shoukry (Environmental Science and Pollution Research, 2022)
This study represents the sustainable/safe consumption of lead glass sludge (LGS) in the fabrication of thermally insulating foamed glass via sintering (750–950º C) and chlorination processes. The impact of selected additives including calcium chloride (CaCl 2 ) and sodium hydroxide (NaOH) on the foaming efficiency and Pb-stabilization has been deeply investigated. LGS is mainly lead silicate material with considerable content of calcium carbonate, which acts as foaming agent during sintering process. The newly developed foamed-materials exhibited thermal conductivity of 0.054–0.136 W/m.K, density of 0.23–1.10 g/cm 3 , porosity of 63.3–92.6%, and compressive strength of 0.10–2.69 MPa. X-ray diffraction proved that the immobilization mechanism was attributed to the transformation of free Pb within LGS into insoluble ganomalite Pb 9 Ca 5 MnSi 9 O 33 phase. Adding NaOH enhanced the foaming process accompanied by a significant reduction in Pb-leaching. Incorporating CaCl 2 has resulted in a retardation in Pb-leaching, which associated with Pb-stabilization and Pb-vaporization. In an attempt to reduce CO 2 -emission, the potential use of alkali-rich-wastewater (AW) as eco-friendly alkali source in lieu of NaOH was studied. Regardless of the variation in Pb-concentrations in leachates, all samples recorded Pb-concentrations lower than the safe limit (≤ 5 mg/l), achieving Pb-immobilization of 95.98–99.87%. The significantly reduced thermal conductivity and enhanced Pb-immobilization efficiency along with the reasonable compressive strength summarize the major innovation presented in this study.

Physical characteristics of heat-dissipating smart marble at Al Masjid Al-Haram, Makkah City, Saudi Arabia - Ahmed Abdel Aal; Hamada Shoukry; Mahmoud A. Sayed; Hamed A. Ghramh (Arabian Journal of Geosciences, 2018)